Métodos de enseñanza en la asignatura de computación en estudiantes de noveno año de educación básica paralelos A, B del Colegio Técnico Pasaje Ciudad de Pasaje provincia de El Oro. - Ríos Toboada, Wilson Efraín (2013)
The methodological development of academic processes in the classroom builds a have positive effects when A range of resources that enable the creation of Educational Environments in which communication allows Comply Learning Objects are used in the classroom. Teaching methods allow Ser v The path that allows the contents reach best way to Students considering and using a number of tools aimed at using technology in the classroom.